N, S co-doped carbon dots based fluorescent "on-off-on" sensor for determination of ascorbic acid in common fruits. (30th August 2018) - Luo, Xueli; Zhang, Wengang; Han, Yong; Chen, Xiumei; Zhu, Li; Tang, Wenzhi; Wang, Jianlong; Yue, Tianli; Li, Zhonghong
Highlights: N, S co-dopants endowed the CDs (N, S-CDs) with high blue fluorescence intensity. The fluorescence of N, S-CDs were quenched as high as 95% by Fe 3+ in 3 min, giving a turn off model. Reduction of Fe 3+ by AA resulted in fluorescence recovery, giving a turn on model. The switchable sensor possessed good selectivity and sensitivity for AA detection. The sensor presented practical measurement of AA content in common fruits. Abstract: A switchable sensor based on N and S co-doped carbon dots (N, S-CDs) was developed to determine ascorbic acid (AA) content in common fruits via fluorescence quenching of N, S-CDs by Fe 3+ (off) and recovery by AA (on). TEM showed that the particle size was 2.35–7.95 nm with an average diameter of 5.12 nm. XPS and FTIR confirmed the presence of –OH, –COOH and –NH2 on N, S-CDs surface. UV–vis and FTIR revealed that the coordination of –COOH and –NH2 on N, S-CDs surface with Fe 3+ accounted for FL quenching, and the release of –NH2 from coordination complexes due to the reduction of Fe 3+ by AA led to partly FL recovery. The sensor allowed detecting AA in the linear range of 10–200 μmol/L with a LOD of 4.69 μmol/L. AA contents in common fruits detected by the sensor were in good agreement with the reference method (P > 0.05), indicating a practical fluorescent sensor for AA detection in common fruits.